(untitled) (Conference on English Language Teaching, 2023)
Speaking is one of the basic skills in learning language. This is a challenge for EFL students in post pandemic by quick transition from virtual to direct learning. Coping with unprecedented situations creates extra stress for EFL students. This happened because they were not used to interacting directly in front of the class. Therefore, the purpose of this study is to investigate the coping strategies that most EFL student’s use to overcome speaking anxiety in post pandemic education. The respondents in this study are 40 students in the first semester of the English Academic Purposes class in Muhammadiyah University of Surakarta. The research method used is qualitative research using two types of questionnaires, namely closed-ended questionnaires and open-ended questionnaires. The result demonstrated that EFL students mostly used the strategies of preparation to cope their anxiety in speaking test.